2023
DOI: 10.3390/ph16050648
|View full text |Cite
|
Sign up to set email alerts
|

Cannabidiol and Minor Phytocannabinoids: A Preliminary Study to Assess Their Anti-Melanoma, Anti-Melanogenic, and Anti-Tyrosinase Properties

Abstract: Currently, there is an increased interest from both scientists and consumers in the application of cannabis/hemp/phytocannabinoids in skin-related disorders. However, most previous investigations assessed the pharmacological properties of hemp extracts, cannabidiol (CBD), or tetrahydrocannabinol (THC), with very few studies focusing on minor phytocannabinoids from hemp. In this context, the current work explored the in vitro anti-melanoma, anti-melanogenic, and anti-tyrosinase effects of cannabidiol (CBD) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 48 publications
0
8
0
Order By: Relevance
“…Methanol and hemp flower extracts inhibit tyrosinase activity and melanin synthesis [22]. The same was observed for minor cannabinoids-CBN, CBC, and CBG [21]. On the other hand, CBD and THC stimulate in vitro tyrosinase activity and melanin synthesis in human epidermal melanocytes [23,24].…”
Section: Biological Activitiesmentioning
confidence: 68%
“…Methanol and hemp flower extracts inhibit tyrosinase activity and melanin synthesis [22]. The same was observed for minor cannabinoids-CBN, CBC, and CBG [21]. On the other hand, CBD and THC stimulate in vitro tyrosinase activity and melanin synthesis in human epidermal melanocytes [23,24].…”
Section: Biological Activitiesmentioning
confidence: 68%
“…The amino acid structure of murine tyrosinase is ca. 85% similar to the human enzyme [ 38 ]. Differences in inhibitory activity toward tyrosinases obtained from different sources were previously detected by our [ 37 ] and other research groups [ 39 , 40 ] and are considered as a significant factor influencing the in vivo activity of newly identified skin-lightening cosmetic ingredients.…”
Section: Resultsmentioning
confidence: 99%
“…Although several cannabis extracts have been reported to exert inhibitory effects on the growth of melanoma cells [15,16], only limited studies explored the antiproliferative activity of the individual cannabinoids. A study reported that CBD and CBG showed the most promising antiproliferative effect (IC 50 = 12.0 and 12.1 µM, respectively) compared to other minor cannabinoids, such as CBN and CBC, in human melanoma A375 cells [17]. It was also reported that CBD had the highest inhibitory effect on the growth of murine melanoma cells (B16F10) with an IC 50 of 80 µM compared to other minor cannabinoids [17].…”
Section: Phytocannabinoids Inhibit the Proliferation Of Murine And Hu...mentioning
confidence: 99%
“…A study reported that CBD and CBG showed the most promising antiproliferative effect (IC 50 = 12.0 and 12.1 µM, respectively) compared to other minor cannabinoids, such as CBN and CBC, in human melanoma A375 cells [17]. It was also reported that CBD had the highest inhibitory effect on the growth of murine melanoma cells (B16F10) with an IC 50 of 80 µM compared to other minor cannabinoids [17]. This trend was in agreement with data from our current study showing that the cytotoxicity of CBD was higher than other minor cannabinoids in murine melanoma cells.…”
Section: Phytocannabinoids Inhibit the Proliferation Of Murine And Hu...mentioning
confidence: 99%